Pengaruh Penilaian Prestasi Kerja Pegawai Terhadap Promosi Jabatan Pada PT. Patra Jasa Kota Palembang - Imam Suroso; Indah Mawarni; Aras Tulip; Tutik Pebrianti; Zein Ghozali (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
This study aims to determine how much influence employee performance appraisal has on promotion at PT.Patra Jasa Palembang City. This study used a survey method (questionnaire). the sample in this study amounted to 30 people. Based on the results of the product moment correlation test for the job performance appraisal variable (X) for promotion (Y), a correlation coefficient value of 0.745 was obtained and based on the guidelines for interpreting the correlation coefficient, it was included in the strong category. This means that the work performance appraisal variable has a strong influence on promotion at PT.Patra Jasa Palembang City. So it can be concluded that the work performance appraisal variable has a significant effect on promotion. Based on the results of the Determination Coefficient Test (R), it can be seen that the influence of the work performance appraisal variable on promotion is 0.555 or 55.5%, while the remaining 44.5% is influenced by other factors. It can be concluded that work performance appraisal has an effect on promotion at PT.Patra Jasa Palembang City.